Synthesis and magnetoelectric properties of multiferroic composites of lead lanthanum zirconate titanate and mesoporous cobalt ferrite. (15th July 2017) - Ai, Ding; Xu, Jianmei; Huang, Can; Zhou, Wei; Zhao, Ling; Sun, Jian; Wang, Qing
Abstract: We describe herein a facile synthetic approach to CoFe2 O4 (CFO)/lead lanthanum zirconate titanate (PLZT) multiferroic composites. The composites were prepared by synthesizing mesoporous CFO through a novel temple-free strategy and subsequent generating PLZT inside mesoporous CFO. The coexistence of both CFO and PLZT phases in the composites was confirmed by XRD. The porosity and pore structures were determined from N2 physisorption analysis and TEM. The composites were found to possess multiferroicity at room temperature and a maximum magnetoelectric voltage coefficient of 36.7 mV/cm Oe. This work is anticipated to pave the way for enhancing the magnetoelectric coupling of multiferroic composite materials. Graphical abstract: